Antitumor and anti-Mycobacterium tuberculosis agents based on cationic ruthenium complexes with amino acids - dos Santos, Edjane R. (2017)
Six new complexes of Ru(II)/phenanthroline/1,4-bis(diphenylphosphino)butane containing amino acids (Glycine, L-Alanine, L-Valine, L-Tyrosine, L-Methionine or L-Tryptophan) were synthesized and characterized by IR, 31P{1H}, 13C and 1H NMR spectroscopies and cyclic voltammetry experiments. These data suggest the presence of diastereoisomers, except for the complex with glycine, amino acid that does not exhibit chiral carbon. The compounds are active against the MDA-MB-231 tumor cells and against Mycobacterium tuberculosis. The cationic ruthenium complexes with amino acids, reported here, show similar cytotoxicity against the MDA-MB-231 tumor cells. When compared with analogs complexes containing 2,2′-bipyridine as ligands, instead of 1,10-phenatroline, the new complexes studied here are, in general, roughly twice more active than the 2,2′-bipyridine ones and their IC50 values comparable with the cisplatin. In addition, low MICs values were obtained against Mycobacterium tuberculosis compared with the reference drugs, cycloserine and ethambutol.